Formal Design and Analysis of a Wastewater Treatment Control System Based on Petri Net - Seno D. Panjaitan; Berlian Sitorus (Journal of Engineering and Technological Sciences, 2012)
This paper proposes a new control design approach for industrial wastewater treatment where its logic control is verifiable. In this research, a treatment control design in a lab-scale was controlled by a microcontroller circuit. The developed system combined anaerobic digestion, aeration and filtration process. Its logic control algorithm was designed by using Signal Interpreted Petri Net. In the logic verification, six analysis properties were satisfied: conflict free (logical process had no conflict behavior), termination (the process could be terminated from any state), non-contradictory outputs, live (any process state could always be reached from other state), deadlock-free, and reversible (the process could always back to initial condition). In the design evaluation, the average value of transparency metrics was 0.984 close to 1 as the best value. The system performance was evaluated by pollutant removal efficiency. The highest removal efficiencies were obtained when each anaerobic and aeration treatment were performed for three days respectively and followed by filtration. Within this condition, the system obtained average removal efficiency 91.7% of Chemical Oxygen Demand and 95.4% of Total Suspended Solids. In terms of electricity consumption, the system needed only 1,857.6 Watt-hour for a batch treatment process.